Evaluating the Economic Water Productivity underfull and deficit irrigation;the case of sesamecrop (Sesumum indicum L.)in woreda Kafta-Humera,Tigrai-Ethiopia - Ataklti Gezae Tewelde (Water Science, 2019)
ABSTRACTSesame crop (Sesumum indicum L.) is one of the cash crops exported from Ethiopia that contributed to the country GDP (gross domestic product). The main objective of this study was to evaluate the economic water productivity (EWP) under full and deficit irrigated sesame crop in wereda Kafta-Humera, Tigrai-Ethiopia. Sesame crop production was particularly related to the summer (Kiremt rainfall). But due to a variation in rainfall distribution in the area, sesame crop production that was harvested by farmers decreased and the economic water productivity of full and deficit irrigated sesame crop could not be evaluated and analyzed previously. To solve this problem and to single out the irrigation water application level that could let the farmers earn high production with high economic water productivity, field-based applied research is needed. Field experimental plots of 2 m x 2 m (area of 4 m2) with three replications were conducted. The leaf area index (LAI), biomass, grain yield, and straw yield were measured at the field level. Moreover, Cropwat-8 model was used to compute irrigation water requirement and scheduling. The experimental results indicated that the average grain yield earned from treatment levels 1 and 2, 3 and 4 were recorded as 11.23, 8.98, 7.17 and 4.70 quintal per hectare, respectively. The results of the Economic water Productivity (EWP) depict a higher value of 0.266 US$/m3 which was obtained in treatment-1 than treatments 2,3 and 4 which have a values of 0.237 US$/m3, 0.212 US$/m3 and 0.159 US$/m3. The result of economic water productivity exhibits that high economic water productivity was earned in treatment 1 which is the one with full irrigation.Abbreviation Economic water productivity (EWP)